The potential use of DNA double-strand breaks detection in various fields of medicine - A. V. Torgashina; A. M. Lila (Современная ревматология)
The article discusses the relevance of determining DNA double-strand breaks (DSBs) using the analysis of γ-H2AX foci as a marker of DNA instability in various conditions. The issues of the formation of DSBs and the peculiarities of their detection in various tissues are highlighted. Changes in the intensity of DSBs formation during the use of radiological diagnostic methods, stress, increased physical exertion, some oncological and rheumatic diseases, as well as the dynamics of DNA repair on the background of various methods of therapy were analyzed.